Hubungan Kausalitas antara Gaya Kepemimpinan dan Iklim Kerja Organisasional Terhadap Employee Engagement Guru di SMK Al Khoiriyah Tulungagung - Diah Ayu Widi Astuti; Sri Wahyuni Mega Hastuti; Edy Swasono (Otonomi, 2020)
Employee engagement or employee attachment to the workplace needs to be deeply instilled because there is a sense of attachment to organizational members both physically, cognitively and emotionally, it is hoped that it can foster a sense of self-motivation in educators and create employee engagement in addition to the existence of a conducive school work climate which will also not be separated from the role of school leadership. This study aims to determine the effect partially and simultaneously between leadership style and organizational work climate on employee engagement. This type of research is descriptive and verification research with a quantitative research approach. The analysis technique used in this research is validity test, reliability test, normality test, classical assumption test, multiple linear regression test and hypothesis test. The results of this study indicate that there is a simultaneous influence between the variables of leadership style and organizational work climate on employee engagement of teachers of SMK Al Khoiriyah Tulungagung. Then the influence of leadership style and organizational work climate on teacher employee engagement was 74.2%. Then partially the leadership style has a positive and significant effect on employee engagement of teachers at SMK Al Khoiriyah Tulungagung and partially the organizational work climate has a positive and significant effect on teacher employee engagement at SMK Al Khoiriyah Tulungagung.